Integrating the value of honesty into the analysis of coal prices, exchange rates, and export profitability in Indonesia (2019–2023) - Khansa Fairus Salsabila; Dessy Noor Farida; Farah Amalia (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
This study aims to analyze the influence of coal prices and rupiah exchange rates on the profitability of Indonesian coal exports in 2019–2023. Using panel data and quantitative methods, this study makes export profitability as a dependent variable, while coal prices and rupiah exchange rates are independent variables. Data was obtained from official sources such as the Direktorat Jenderal Mineral dan Batubara, the Badan Pusat Statistic (BPS), and the company’s financial statements on the Indonesia Stock Exchange with a population of data, namely the reference coal price listed on the BPS for the 2019-2023 period and the selected sample in the form of data from 8 companies within a period of 5 years. Panel data regression analysis was used to find out how coal prices and exchange rates affect the profitability of coal exports in Indonesia. The results of the study show that coal prices have a positive and significant effect on export profitability, while the rupiah exchange rate does not have a significant impact because the majority of transactions use US dollars. These findings provide insight for policymakers in maintaining the stability of the coal export sector amid global market dynamics.